Enhancing the Efficacy of Chloramphenicol Therapy for Escherichia coli by Targeting the Secondary Resistome - Mosaed Saleh A. Alobaidallah; Vanesa García; Sandra M. Wellner; Line E. Thomsen; Ana Herrero-Fresno; John Elmerdahl Olsen (MDPI AG, 2024)
The increasing prevalence of antimicrobial resistance and the limited availability of new antimicrobial agents have created an urgent need for new approaches to combat these issues. One such approach involves reevaluating the use of old antibiotics to ensure their appropriate usage and maximize their effectiveness, as older antibiotics could help alleviate the burden on newer agents. An example of such an antibiotic is chloramphenicol (CHL), which is rarely used due to its hematological toxicity. In the current study, we employed a previously published transposon mutant library in MG1655/pTF2::blaCTX-M-1, containing over 315,000 unique transposon insertions, to identify the genetic factors that play an important role during growth in the presence of CHL. The list of conditionally essential genes, collectively referred to as the secondary resistome (SR), included 67 genes. To validate our findings, we conducted gene knockout experiments on six genes: arcA, hfq, acrZ, cls, mdfA, and nlpI. Deleting these genes resulted in increased susceptibility to CHL as demonstrated by MIC estimations and growth experiments, suggesting that targeting the products encoded from these genes may reduce the dose of CHL needed for treatment and hence reduce the toxicity associated with CHL treatment. Thus, the gene products are indicated as targets for antibiotic adjuvants to favor the use of CHL in modern medicine.